Cytogenetic results of recurrent spontaneous abortions in Turkey - Yuce, Huseyin; Tekedereli, Ibrahim; Elyas, Halit (Int Scientific Literature, Inc, 2007)
Background: Recurrent spontaneous abortion is defined as at least three consecutive pregnancy losses, occuring in 10% of all pregnancies. In tile etiology of recurrent spontaneous abortion, a wide variety of abnormalities, such as anatomic, endocrinologic, and genetic abnormalities, has been reported. The aim of this study was to compare karyotyping results of couples with recurrent spontaneous abortions. This may contribute to elucidating the genetic basis of this condition and warn physicians of the cytogenetic abnormalities in cases with recurrent spontaneous abortions. Material/Methods: The cytogenetic results of patients with at least two abortions referred to Firat (Euphrates) University, College of Medicine, Department of Medical Biology and Genetics in the six-year period between 2000-2005 were reviewed retrospectively. Results: Of a total of 421 couples (842 patients), 23 men (2.73%) and 8 women (0.95%) had abnormal karyotypes. Balanced and unbalanced karyotypes and polymorphisms had nates of 1.06%, 0.71%, and 1.9%, respectively, the total rate being 3.68%. Conclusions: These data show that cytogenetic evaluation is necessary for all accurate approach to elucidating tile causes of recurrent spontaneous abortion, and physicians should also be careful of the diversity of chromosomal abnormalities that play important roles in the etiology of recurrent spontaneous abortion.
Keywords: cytogenetics; chromosome aberrations; karyotyping; spontaneous abortion